Étude expérimentale des macrotraces d’utilisation sur les tranchants des bifaces - Émilie Claud; Michel Brenet; Serge Maury; Vincent Mourre (Les Nouvelles de l’Archéologie, 2009)
We describe an experimental program involving flint handaxes and edge damage resulting from their use. The usewear traces are compared with those commonly observed on unretouched flakes. Since the experimental traces show the same characteristics for the same utilization and different features for distinct uses, they can be considered as good criteria for determining the modes of use of archeological handaxes. We provide the results of a comparison of this experimental reference collection to the usewear data observed on handaxes from the Middle Paleolithic sites of La Graulet and La Conne de Bergerac (Dordogne). These usewear data, and their relationships to morphological features, show that there is a link between handaxe morphology and their mode of use. These results call into question the common notion that handaxes were multipurpose tools.